Latitudinal diversity of planktonic copepods in the Eastern Pacific: overcoming sampling biases and predicting patterns - Rivera, Reinaldo; Escribano, Ruben; González, Carolina E.; Pérez-Aragón, Manuela (Frontiers in Ecology and Evolution, 2024)
Gradients of latitudinal diversity are one of the biogeographic features calling the most attention in ecology and macroecology. However, in pelagic communities of the marine environment, geographic trends and patterns are poorly known. We evaluated the latitudinal variation in species richness of marine planktonic copepods in the Eastern Pacific using spatial statistical models and approaches that mitigate and account for biases in occurrence data. A Boosted Regression Tree (BRT) and regression-Kriging based models allowed us to estimate and predict alpha diversity in poorly sampled regions, whereas beta diversity patterns were assessed using generalized dissimilarity analysis (GDM). Species richness showed a bimodal pattern, with a maximum of 291 species in the Northern Hemisphere and Tropical Eastern Pacific Ocean. particulate organic carbon, salinity (max), spatial autocovariate, range of salinity and temperature, and mixed layer depth, explained 85.2% of the latitudinal variability of copepods. Beta diversity was structured into four macrozones associated with the main water masses of the North and South Pacific. Our analytical approaches can overcome the limitations of data gaps, 2 predicting greater diversity in subtropical and coastal areas, while providing insights into key drivers modulating spatial diversity patterns.